Recurrent frameshift neoantigen vaccine elicits protective immunity with reduced tumor burden and improved overall survival in a Lynch syndrome mouse model - Gebert, Johannes; Gelincik, Ozkan; Özcan-Wahlbrink, Mine; Marshall, Jason D.; Hernandez Sanchez, Alejandro; Urban, Katharina; Long, Mark; Cortes, Eduardo; Tosti, Elena; Katzenmaier, Eva-Maria Katharina; Song, Yurong; Elsaadi, Ali; et al. (Gastroenterology, 2021)
DNA mismatch repair deficiency drives microsatellite instability (MSI). Cells with MSI accumulate numerous frameshift mutations. Frameshift mutations affecting cancer-related genes may promote tumorigenesis and, therefore, are shared among independently arising MSI tumors. Consequently, such recurrent frameshift mutations can give rise to shared immunogenic frameshift peptides (FSPs) that represent ideal candidates for a vaccine against MSI cancer. Pathogenic germline variants of mismatch repair genes cause Lynch syndrome (LS), a hereditary cancer syndrome affecting approximately 20-25 million individuals worldwide. Individuals with LS are at high risk of developing MSI cancer. Previously, we demonstrated safety and immunogenicity of an FSP-based vaccine in a phase I/IIa clinical trial in patients with a history of MSI colorectal cancer. However, the cancer-preventive effect of FSP vaccination in the scenario of LS has not yet been demonstrated.